HUBUNGAN BUDAYA ORGANISASI DENGAN TINGKAT STRES DAN BURNOUT PERAWAT DI RUMAH SAKIT: SYSTEMATIC REVIEW - Grace Irma Gorean; Enie Novieastari; Andi Amalia Wildani; Dewi Gayatri (Poltekkes Kemenkes Bandung, 2025)
Organizational culture is a summary of shared values, beliefs, or perceptions held by employees in an organization or organizational unit and it can influence staff attitudes and behaviors. This has an impact on the quality of life of nurses, including health, emotional exhaustion, job satisfaction, work stress. The purpose of this study is to convey the results of the exploration related to the relationship between organizational culture and stress levels and nurse burnout in the Hospital. This research method is a detailed analysis using the PRISMA flow diagram, Literature search in several databases, namely Proquest, Science Direct, Taylor & Francis Online, Pubmed, Sage, Whiley and Scopus which are published. Article quality assessment using the JBI Joanna Briggs Institute Critical Appraisal Checklist for Analytical Cross Sectional Studies. Eleven articles were identified and analyzed that met the inclusion criteria; Articles have Abstract and Full text, Search type in the database with journal articles, published in English, articles published in the last 10 years 2014 - 2024, Articles that discuss organizational culture; positive organizational culture consisting of; Open and transparent communication, strong social support, Good teamwork, trust and appreciation for nurses, Safe and comfortable work environment, articles discussing stress levels and burnout of nurses in hospitals. Exclusion criteria: Articles cannot be accessed as full text, books, Literature reviews, theses, books, Research articles that do not discuss organizational culture; Positive organizational culture consisting of; Open and transparent communication, Strong social support, Good teamwork, Trust and appreciation for nurses, Safe and comfortable work environment, Research articles that do not discuss stress levels and burnout of nurses in hospitals. The literature search started in March 2024, with the results of the synthesis, namely Organizational culture has a relationship with stress levels and burnout in nurses in hospitals. In general, it can be concluded from the literature search data, namely Organizational culture greatly influences nurse burnout, therefore a positive organizational culture is needed in health services, a positive organizational culture is less likely to indicate stress levels and burnout in nurses.